Kombinasi Metode Analytic Hierarchy Process dan Weighted Product pada Rekomendasi Pemilihan Tempat Kost - Aso Sudiarjo; Missi Hikmatyar (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The application of information technology has been widely implemented in various aspects of life, including the property sector. With the number of boarding houses in the city of Tasikmalaya and the high demand for consumers, namely students, students, overseas employees in using boarding house rental services for temporary housing in the city of Tasikmalaya, consumers must be careful in choosing a boarding house that matches the desired criteria. . The problem that occurs is that sometimes consumers often feel confused when they have to decide which boarding house to rent according to their wishes. Therefore, this study aims to assist consumers in determining the right boarding house and according to their needs. The system is built using a combination of AHP (Analytic Hierarchy Process) and WP (Weighted Product) methods. The AHP method is used to calculate the weight of each criterion, while the WP method is used in ranking to get the best boarding alternative. There are 6 criteria used in this system, namely: price, type of boarding house, facilities, location, parking area and security. While WP was chosen because it has the ability to analyze alternatives into a form of ranking with a fast and easy process. The method used in developing this application is adapted from the SLDLC (System Development Life Cycle) method. The results of this study are in the form of an application prototype that can recommend a boarding house as needed